A 6-week mindfulness-acceptance-commitment intervention to improve professional ballet dancers` psychological states around performance - Harrison, C.; Ruddock, S.; Mayes, S.; Cook, J.; O'Halloran, P.; Ferrar, K.; Li, X.; Ruddock, M. (Journal of Dance Medicine & Science, 2024)
Background: Mindfulness and acceptance-based approaches have been trialled in professional sport. The present pilot study was a randomized controlled trial with professional ballet dancers investigating the effectiveness of the Mindfulness-Acceptance-Commitment (MAC) approach, developed for athletes, compared to an education program which included topics relevant to ballet and performance. Methods: Participants included 16 professional ballet dancers (2 men and 14 women) who were randomly assigned into either the MAC or education group for 1 session per week, for 6 weeks. Participants were assessed pre-and post-intervention using the Mindfulness Inventory for Sport (MIS) and the Acceptance Action Questionnaire (AAQ-II). Within 2 weeks of the final mindfulness session, all participants completed a semi-structured interview. Results: No differences were found when comparing the questionnaire responses between pre- and post- intervention, nor between the MAC group and the control group at post intervention for all subscales. Although dancers reported in the interviews that the sessions were valuable, they advised their ability to dedicate time to mindfulness ongoing would be challenging. Conclusions: Mindfulness interventions, as explored in this study, show promise to promote the well-being of professional ballet dancers. For consistent and ongoing mindfulness practice, future designs should seek to embed mindfulness practice into dancer and company schedules.